Internet protocol MANET vs named data MANET: A critical evaluation - Alubady, Raaid; Al-Samman, Mohammed; Hassan, Suhaidi; Arif, Suki; Habbal, Adib M. Monzer (2015)
Many researches have been done in the field of mobile networking, specifically in the field of ad-hoc networks.The major aim of these networks is the delivery of data to a given node at the destination, irrespective of its location.Mobile Ad-hoc Network (MANET) employs the traditional TCP/IP structure to provide end-to-end communication between nodes (we named this type of architecture is IP-MANET).However, due to their mobility and the limited resource in wireless networks, each layer in the TCP/IP model requires redefinition or modifications to function efficiently in MANET. Named Data MANET (NDMANET) architecture is a recently emerging research area. The in-network chunk-based caching feature of NDN is beneficial in coping with the mobility and intermittent connectivity challenges in MANETs.In the natural disaster field, MANET is considered a challenging task because of the unpredictable changes in the network topology due to the absence of any centralized control.The goals of this paper have two ways: first, this study provides a performance comparison of IP-MANET to ND-MANET in terms of throughput, delay, and packet loss.While the second contribution is to identify which architecture has an impact on the natural disaster (i.e., Flooding disaster) in rural areas and suggests which one may perform better.For experimental purposes, our analyses IP-MANET and ND-MANET by extensive simulations in the NS 3 simulator under a number of different network scenarios, and show that how number of nodes and variety packets size affect their performance.